Numerical study of heat transfer enhancement in asphalt collector using CuO nanofluid - Hashim, Ghasaq Adheed (2014)
This study investigates the heat transfer enhancement in asphalt collector by using CuO nanofluid. In this study the first approach is based on increasing the heat gain which is captured by solar energy on asphalt pavement. The second approach is related to accelerate the period of snow melting. Numerical simulation method has been used to predict the temperature distribution in the asphalt collector. The study was conducted at unsteady state, laminar fluid flow with small and large scale of geometry. Certain boundary conditions and assumptions to solve the governing equations were implemented by using finite volume method. Computational fluid dynamics software involves ANSYS FLUENT 14.0 was employed to perform the investigation numerically. Using nanofluid is considered as a positive way to improve the performance of melting system. The CuO Nanofluid from 1 to 4% volume fraction with particle diameter of 50 nm dispersed in a base fluid (water) were used to improve the heat transfer of asphalt collector and thus resulting in an augmentation of efficiency of asphalt collector. The rise in temperature of nanofluid as a result of flow through asphalt pavement was used as an indicator of efficiency enhancement of heat capture. The results of simulation for both small and large scale geometries show that the use of nanofluid can significantly enhance the efficiency of heat capture by bringing high amount of solar energy out. It is also noticed that the asphalt collector provides us a better alternative method for snow melting. Asphalt pavement temperature distribution was evaluated and the non-uniform temperature in the asphalt pavement is noticeable.